PEMANFAATAN SIMBOL SUCI HINDU DALAM INDUSTRI PARIWISATA BALI - I Gusti Ketut Widana (Pascasarjana Universitas Hindu Indonesia, 2017)
In fact, whatever exists, both outside and inherent in the human self is also a series of symbolic nodes which, when interpreted, will puncture or bring about various meanings. Meanings derived from the results of observation, reading, appreciation or even agreement on what is behind the symbols. The essence of the symbol is not merely in what appears in the form of material matter, but rather to what is â€œhiddenâ€ behind the embodiment itself. Likewise with toolsrelated to the implementation of ceremony / upakara yadnya very rich symbol, and certainly has a sacred value (sacred) which is only limited to be used in establishing a relationship to Hyang Widhi bhakti and all his manifestations. If then because of the unique aesthetic look of the media the sacred symbol is then used for the benefit of the tourism industry, as long as it remains in the context as it is displayed in terms of the implementation of yadnya, certainly not a problem. But if the sacred symbol media is only manipulated to be taken in aesthetic terms and then packaged as part of commercialization, then in addition to the risk of harassment and even desecration, is also likely to rip the religious emotions of Hindus who strongly believe the sanctity of the symbol as a sacred device that is oriented transcendental, The appearance of financially sourced material for sale.